An investigation into how small businesses can gain competitive advantage through collaborative supply chain models - Tshabangu, Onalenna (My University, 2021)
The failure rate of SMMEs in South Africa is alarming and it is impacting the economy negatively (Herrington, Kew, & Mwanga, 2017). SMMEs discontinuance is a multi-faceted problem that requires multiple mitigation strategies, as it stems from multiple social, economic, political, financial, infrastructure and supply chain challenges (Bureau for Economic Research, 2016). The primary reasons for small businesses discontinuance include: (a) lack of access to and efficient use of working capital; (b) access to and efficient use of infrastructure; (c) business profitability; (d) access to and efficient use of finances (Bureau for Economic Research, 2016). This research demonstrates how all four challenges (a, b, c and d above) can be mitigated significantly through the implementation of different collaborative supply chain models. This was done by developing an investigational framework that links supply chain collaboration to the sustainability of SMMEs in the South African context. The investigative framework was then tested by formulating and quantitatively evaluating 12 hypotheses with the use of a questionnaire. The participants were categorised into three main parts namely, (a) position in company, (b) industry they operate in and (c) the size of their organisation. Once the research results were obtained, they were interpreted and a conclusion made affirming the framework. The research provided clear answers for the central question, as well as the five sub-questions which sought to assess validity of the investigational framework and its possible application in the South African context
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering,2021